How loyalty extends across product categories. Issue 1 (14th August 2021) - Grasby, Alicia; Corsi, Armando; Dawes, John; Driesener, Carl; Sharp, Byron
Abstract: Fifty years ago, Gerald Goodhardt's analysis of audience duplication across television programs led to the discovery of the Duplication of Viewing law. This law was then extended to describe and predict customer sharing within product categories: the Duplication of Purchase Law. Many replications and extensions documented the law‐like status of this generalisation, providing important insight into how brands compete and the composition of consumers' repertoires. In this article we build on that seminal research, using Duplication of Purchase as an analytical method to measure loyalty across categories, or, in other words, the purchasing of brand extensions. Brand extensions are commonly cited as a way to capitalise on brand equity, and when asked, respondents often report high intentions to purchase brand extensions. However, the actual cross category buying of brand extensions has not been systematically examined. In this research we analyse panel data to understand whether purchasing a brand in one category does in fact increase the likelihood of a brand being bought in a second category. The study finds that a consumer who purchases from two categories is on average 2.4 times more likely to purchase a brand extension in the second category if they had purchased the same brand in the other category. This effect is larger for brands spanning similar, or complementary categories. Therefore, for many brand extensions the cross‐category loyalty effect is much more modest.